CE-02 Peer approaches to lupus self-management (pals): a novel lupus peer mentorship intervention. (31st August 2016) - Williams, Edith; Egede, Leonard; Oates, James
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that is associated with increased morbidity, mortality, health care costs and decreased quality of life. While evidence-based self-management interventions that incorporate both social support and health education have reduced pain, improved function, and delayed disability among lupus patients, African Americans and women are still disproportionately impacted by lupus. In the United States, African Americans have three to four times greater prevalence of lupus, risk of developing lupus at an earlier age, and lupus-related disease activity, damage, and mortality compared with Caucasians, with the highest rates experienced by African American women. Persistent disparities may be due to the non-responsiveness of existing programs to the unique needs of African Americans and/or women with lupus. Peer mentoring interventions are effective in other chronic conditions that disproportionately affect minorities, such as diabetes, HIV, and kidney disease, but there is currently no empirically tested peer mentoring intervention developed for SLE patients. Materials and methods: A literature review, needs assessment, and interviews with patients guided the development of a peer mentor training manual and a peer mentoring intervention. African American women with lupus are being recruited from the SLE database at the Medical University of South Carolina. Seven mentors will be trained and paired with 21 mentees to provide modelling and reinforcement to participants by telephone for at least 60 minutes every week for 12 weeks. The goal of mentorship will be to encourage mentees to engage in activities that promote the learning of disease self-management skills and to support the mentees' practice of these learned skills during the three-month intervention period. Mentee outcomes of health-related quality of life, self-management (including treatment adherence), and disease progression (including disease activity, damage, and cytokine balance) will be obtained at baseline, mid-intervention (6 weeks from baseline), and immediately post-intervention (12 weeks from baseline), using validated tools. Descriptive statistics and effect sizes will be calculated to determine clinically important (>0.3) changes. Results: This study is currently in progress. Preliminary results will be shared. Conclusions: Given the success of the peer mentoring approach in other chronic conditions that disproportionately impact minorities, and its responsiveness to the needs of this unique population, this intervention could result in health improvements that have not been attainable with other interventions. This could lead to significant reductions in disparities and have considerable public health impact. Acknowledgements: This project was supported by the South Carolina Clinical & Translational Research (SCTR) Institute, with an academic home at the Medical University of South Carolina CTSA, NIH/NCATS grant number UL1TR001450. The contents are solely the responsibility of the authors and do not necessarily represent the official views of the NIH or NCATS.